THE STRUCTURAL BEHAVIOR OF FERRIC AND FERROUS IRON IN ALUMINOSILICATE GLASS NEAR META-ALUMINOSILICATE JOINS - Mysen B.O. (My University, 2006)
Iron-57 resonant absorption Mossbauer spectroscopy was used to describe the redox relations and structural roles of Fe3+ and Fe2+ in meta-aluminosilicate glasses. Melts were formed at 1500 °C in equilibrium with air and quenched to glass in liquid H2O with quenching rates exceeding 200 °C/s. The aluminosilicate compositions were NaAlSi2O6, Ca0.5AlSi2O6, and Mg0.5AlSi2O6. Iron oxide was added in the form of Fe2O3, NaFeO2, CaFe2O4, and MgFe2O4 with total iron oxide content in the range ?0.9 to ?5.6 mol% as Fe2O3. The M?ssbauer spectra, which were deconvoluted by assuming Gaussian distributions of the hyperfine field, are consistent with one absorption doublet of Fe2+ and one of Fe3+. From the area ratios of the Fe2+ and Fe3+ absorption doublets, with corrections for differences in recoil-fractions of Fe3+ and Fe2+, the Fe3+?Fe is positively correlated with increasing total iron content and with decreasing ionization potential of the alkali and alkaline earth cation. There is a distribution of hyperfine parameters from the M?ssbauer spectra of these glasses. The maximum in the isomer shift distribution function of Fe3+, ?Fe3+, ranges from about 0.25 to 0.49 mms (at 298 K relative to Fe metal) with the quadrupole splitting maximum, ?Fe3+, ranging from ?1.2 to ?1.6 mm/s. Both ?Fe3+ and ?Fe2+ are negatively correlated with total iron oxide content and Fe3+?Fe. The dominant oxygen coordination number Fe3+ changes from 4 to 6 with decreasing Fe3+?Fe. The distortion of the Fe3+-O polyhedra of the quenched melts (glasses) decreases as the Fe3+?Fe increases. These polyhedra do, however, coexist with lesser proportions of polyhedra with different oxygen coordination numbers. The ?Fe2+ and ?Fe2+ distribution maxima at 298 K range from ?0.95 to 1.15 mm s and 1.9 to 2.0 mm/s, respectively, and decrease with increasing Fe3+?Fe. We suggest that these hyperfine parameter values for the most part are more consistent with Fe2+ in a range of coordination states from 4- to 6-fold. The lower ?Fe2+-values for the most oxidized melts are consistent with a larger proportion of Fe2+ in 4-fold coordination compared with more reduced glasses and melts. ? 2006 Elsevier Inc. All rights reserved.
Keywords: ABSORPTION; ALUMINOSILICATE; CHEMICAL COMPOSITION; IONIZATION; IRON; IRON OXIDE; MOSSBAUER SPECTROSCOPY; SILICATE MELT